Influence of Tree Geometry on Growth and Yield of Mungbean (Vigna radiata L.) under Gamhar (Gmelina arborea Roxb.) based Agroforestry System - Dharani, B.; Yadav, Ram Prakash; Tiwari, Prabhat; Dobriyal, Manmohan J.; Kamini (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during kharif (June to September) 2022–23 at Rani Lakshmi Bai Central Agricultural University, Jhansi, Uttar Pradesh, India to evaluate effect of Gmelina arborea geometry on the growth and yield of mungbean, tree growth, biomass, carbon storage and assessing the economic feasibility of the agroforestry systems. The experiment was designed for intercropping of one mungbean high yielding varieties viz., IPM 205-7 (Virat) sown in June with Gmelina arborea. The treatments for gamhar and mungbean are as follows: T1-Vigna radiata sole crop; T2-Gmelina arborea sole tree (5×5 m2); T3-Gmelina arborea sole tree (5×4 m2); T4-Gmelina arborea sole tree (5×3 m2); T5-Gmelina arborea (5×5 m2)+Vigna radiata; T6-Gmelina arborea (5×4 m2)+Vigna radiata; T7-Gmelina arborea (5×3 m2)+Vigna radiata. Experiment was designed in randomized block design (RBD) with seven treatments and five replications. The effect of different spacing patterns viz., S1-5×5 m2, S2-5×4 m2, S3-5×3 m2 in 2 year old Gamhar plantation with seven treatments combinations on mungbean was studied at the Forestry Research Farm, RLBCAU, Jhansi. The maximum number of branches plant-1 (8.04), number of trifoliate leaves plant-1 (11.96), number of seeds pod-1 (12.32), grain yield (0.73 t ha-1) and straw yield (2.13 t ha-1) was recorded in mungbean sole crop. The plant height (62.51 cm) was recorded highest in mungbean intercrop in 5×3 m2 gamhar spacing. The maximum girth (27.38 cm) of trees was recorded in 5×5 m2 gamhar spacing mungbean intercrop. The tree height (6.01 m) and benefit cost ratio (2.67) was observed maximum in 5×4 m2 gamhar spacing with mungbean intercrop.